FPO Member Farmer Empowerment: Socio-economic Insights via Canonical Correlation Analysis (Indian Journal of Extension Education, 2024)
A multivariate analysis was undertaken in this study using canonical correlation analysis. The aim was to investigate the association between socio-economic variables and the empowerment of member farmers who are part of Farmer Producer Organizations (FPOs). A total of 186 member farmers were selected from 6 FPOs located in two districts, namely Kalahandi and Cuttack, in Odisha. The selection process involved choosing 5% of member farmers from each FPO, with 4 from Kalahandi and 2 from Cuttack, using proportionate random sampling. Data was collected through a well-structured and pre tested interview schedule. The analysis revealed that 30.98 per cent of the variance in empowerment was attributed to the socio-economic variables considered in the present study. The findings indicated that an increase in education level and active participation in FPO activities led to enhanced social empowerment among farmers. Similarly, factors such as larger family size, greater market orientation, and larger cultivated land area were associated with increased economic empowerment. Additionally, the study found that a higher extent of cultivated land contributed to cultural empowerment among the farmers.